Deviations from tidal torque theory: Evolution of the halo spin–filament alignment. Issue 4 (17th February 2021) - López, Pablo; Cautun, Marius; Paz, Dante; Merchán, Manuel; van de Weygaert, Rien
ABSTRACT: The alignment between halo spins and the cosmic web is still poorly understood despite being a widely studied topic. Here, we study this alignment within the context of tidal torque theory (TTT) and deviations from it. To this end, we analyse the evolution of the shape and spin direction of proto-haloes, i.e. of all the volume elements associated to a z  = 0 halo, with respect to the present-day filaments. We find that the major axis of proto-haloes undergoes a major change, from being strongly perpendicular to the filament spine in the initial conditions, to being preferentially aligned at the present time. In comparison, the spin orientation shows only a mild evolution: it starts slightly parallel to the filament spine, but the subsequent evolution, up to z ∼ 1, gradually changes its orientation to preferentially perpendicular. In order to analyse these signals in the TTT framework, we split the haloes according to their net spin growth with respect to the median TTT expectation, finding a clear correlation with the spin–filament alignment. At the present time, haloes whose spin grew the most are the ones most perpendicular to the filament spine, while haloes whose spin grew below the median TTT expectation are typically more aligned. The dependence of spin directions on net spin growth is already present in the initial conditions, and gets further modified by late-time, z < 2, evolution. Also, spin directions mildly deviate from the TTT predictions even at high redshift, indicating the need for extensions to the model.